2002
DOI: 10.1002/bit.10489
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of enhanced thermal stability of an alkaline protease with engineered twin disulfide bridges and calcium‐dependent stability

Abstract: The thermal stability of a cysteine-free alkaline protease (Alp) secreted by the eukaryote Aspergillus oryzae was improved both by the introduction of engineered twin disulfide bridges (Cys-69/Cys-101 and Cys-169/Cys-200), newly constructed as part of this study, and by the addition of calcium ions. We performed an extensive kinetic analysis of the increased thermal stability of the mutants as well as the role of calcium dependence. The thermodynamic activation parameters for irreversible thermal inactivation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…We also found that the thermostability of both AprA and AprA-PPC was also significantly improved by the addition of Ca 2+ . Similar results were also observed for several alkaline proteases from organisms such as B. lehensis 16 , B. pumilus 57 , A. oryxae 81 , S. koyangensis 25 , and Conidiobolus brefeldianus 79 . Ca 2+ is considered to effect protease thermostability by strengthening the intramolecular interactions of the enzyme and by binding of Ca 2+ to autolysis sites 79 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also found that the thermostability of both AprA and AprA-PPC was also significantly improved by the addition of Ca 2+ . Similar results were also observed for several alkaline proteases from organisms such as B. lehensis 16 , B. pumilus 57 , A. oryxae 81 , S. koyangensis 25 , and Conidiobolus brefeldianus 79 . Ca 2+ is considered to effect protease thermostability by strengthening the intramolecular interactions of the enzyme and by binding of Ca 2+ to autolysis sites 79 .…”
Section: Discussionsupporting
confidence: 82%
“… B. subtilis WB600 pMA5 48 4935.5 102.8 B. pumilus 56 B. subtilis WB600 pSU 48 32.8 0.7 B. subtilis 65 B. subtilis DB100 pUB110 10 26.0 2.6 B. pumilus 80 B. subtilis DB430 pBSMuL2 72 5800.0 80.6 Bacillus sp. 79 B. subtilis DB104 pAH101NC 24 30.0 1.3 B. subtilis 57 B. subtilis Bios11 pUB110 11 24.5 2.2 A. oryzae 81 P. pastoris GS115 pPIC9K 120 47.5 0.4 B. stearothermophilus 12 P. pastoris GS115 pGAPZαB 72 41.3 0.6 A. nidulans 58 P. pastoris X33 pPICZαA 48 1.0 <0.1 B. cereus 82 P. pastoris X33 pPICZαA 72 122.6 1.7 A. sojae 83 P. pastoris KM71 pPIC9K 72 400.4 5.6 B. stearothermophilus 27 E. coli XL1-Blue pTrcHis 24 22 0.9 S. maltophilia …”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the calcium ions occupying calcium binding-site III, the loop region 56-69 is stabilized by the disulfide bridge connecting residues 8 and 60. Engineered disulfide bridges producing a similar effect on protein stability as calcium ions have been also reported for subtilisin BPN¢ or alkaline protease [37,38]. However, under calcium saturation ( Figs 5 and 6), the introduced disulfide bridge seems to have an additional stabilization effect.…”
Section: The Disulfide Bridge In G8c/n60c Mimics the Occupation Of Casupporting
confidence: 66%
“…Following this concept, disulfide bridges should not influence unfolding processes. Indeed, there are only a few reports of successful stabilization against irreversible unfolding by disulfide linkage in the literature [36–38]. The high stabilization effect of the disulfide bond in G8C/N60C can best be explained by the assumption that unfolding and/or autoproteolysis via the unfolding intermediate is hampered.…”
Section: The Disulfide Bridge In G8c/n60c Mimics the Occupation Of Camentioning
confidence: 99%
“…Thus, the replacement of the free cysteine residues of FDHs is not the best strategy to improve enzyme chemical stability. As a feasible strategy, the construction of disulfide bonds is widely applied in improving the thermal stability of enzymes such as α-amylase (8), xylanases (9), alkaline protease (10), and lipases (11). There are no reports that disulfide bonds can be formed in wild-type FDHs.…”
Section: Introductionmentioning
confidence: 99%